Determinants of Sexual Behavior in Adolescent Girls Aged 15-19 Years Old in Indonesia - Andriati Reny Harwati; Puji Laksmini (Sarana Ilmu Indonesia (salnesia), 2022)
Premarital sexual behavior in adolescent is currently a concern because it may have negative impacts for the health of the teenagers. This study’s aim was to obtain factors associated with premarital sexual behavior (intercouse) in adolescent girls aged 15-19 years old in Indonesia. This study used the 2017 IDHS data with a cross sectional design. The research sample was 7213 respondents who was taken based on the research inclusion criterias. The results of this study explained that 79 female adolescents aged 15-19 years old who have had premarital sexual intercourse (1,1%). The results of the bivariate analysis used Chi-Square test revealed that the factors associated with premarital sexual behavior in adolescent girls were education (p-value 0,001), attitudes towards premarital sexual behavior (p-value 0,000), drug use (p-value 0,000), alcohol consumption (p-value 0,000), friends who have premarital sex (p-value 0,000), and having a boyfriend (p-value 0,000). The results of multivariate analysis with multiple logistic regression test, known factors related to premarital sexual behavior in adolescent girls, namely attitudes toward premarital sexual behavior (p-value 0,000) and alcohol consumption (p-value 0,002). The most dominant variable in this study is the attitude towards premarital sex behavior. In this study, knowledge about reproductive health and having a boyfriend are confounding variables. Knowledge about reproductive and sexuality health in adolescents has to be increased so adolescents have a positive sexuality behavior.